Multi-response optimization of TiO2/EG-water nano-coolant using entropy based preference indexed value (PIV) method. (31st May 2019) - Yahya, Syed Mohd; Asjad, Mohammad; Khan, Zahid A
Abstract: Nano-coolants, being excellent cooling medium, are primarily used in heat transfer applications. Their use in heat transfer applications has revolutionized the thermal industries because they have huge potential for extracting heat as compared to other conventional fluids such as water, ethylene glycol, oil, etc. However, their viscosity may impose a limitation, particularly in case of forced convective heat transfer, since increase in viscosity increases the required pumping power. Present study is mainly focussed on the preparation of stable, low viscosity TiO2 /EG-water nano-coolant. Three process parameters i.e. sonication time, concentration of nano-particles, and pH value each at three levels are considered. Experimental data pertaining to two response variables i.e. Zeta potential (Z) and viscosity ( μ ) of the nano-coolants are collected using the Taguchi's L9 orthogonal array. Multi-response optimization is carried out using the following methods: (i) combined Entropy and Preference Indexed Value (PIV) multi-criteria decision making (MCDM) methods, (ii) analysis of mean (ANOM), and (iii) analysis of variance (ANOVA). It is found that within the investigated range of the process parameters, the optimal combination of the process parameters which maximizes the Zeta potential (Z) and minimizes the viscosity ( μ ) simultaneously is A3 B2 C3 (i.e. sonication time = 120 min, concentration of nanoparticles = 0.03 % by vol, and pH value = 11). Furthermore, ANOVA results indicate that sonication time is the most significant process parameter followed by pH value, and concentration of nanoparticles.